2017
DOI: 10.18203/2394-6040.ijcmph20175771
|View full text |Cite
|
Sign up to set email alerts
|

Burden of diabetes and hypertension among people attending health camps in an urban area of Kancheepuram district

Abstract: Background: Diabetes and hypertension are among the most common non-communicable diseases affecting our population. They are the important risk factors for cardiovascular morbidity and mortality. The aims and objectives of the study were to determine the burden of diabetes and hypertension among people attending health camps in an urban area of Kancheepuram district. Formulation of suitable preventive measures based on the inferences from the study.Methods: A cross- sectional record based study was done on 825… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…[14][15][16] However study by Kishore et al 14.1%, Singh et al 10.36% and Hariharan et al 10.7% obtained low prevalence than present study. [17][18][19] The prevalence of hypertension was found to be 11.1% in rural area which was comparable to study by Ghosh 10.6%, Singh et al 10.36%. 19,20 A Higher prevalence to the present study, was reported in studies by Marinayakanakoppalu et al 25.0%, Ismail et al 18.3%.…”
Section: Discussionsupporting
confidence: 74%
“…[14][15][16] However study by Kishore et al 14.1%, Singh et al 10.36% and Hariharan et al 10.7% obtained low prevalence than present study. [17][18][19] The prevalence of hypertension was found to be 11.1% in rural area which was comparable to study by Ghosh 10.6%, Singh et al 10.36%. 19,20 A Higher prevalence to the present study, was reported in studies by Marinayakanakoppalu et al 25.0%, Ismail et al 18.3%.…”
Section: Discussionsupporting
confidence: 74%
“…World Health Organization (WHO) records that among the total deaths 2% of deaths are due to diabetes in India [3]. Diabetes and hypertension is found to be the common non-communicable disease [4], [5]. Diabetes counts to 46.2% and hypertension counts to 4% of total deaths [6].…”
Section: Introductionmentioning
confidence: 99%
“…If unmitigated, the total number of noncommunicable disease related deaths is estimated to reach 52 million yearly by 2030 [3]. The most common noncommunicable diseases are diabetes and hypertension [4], [5], which account for nearly 46.2% and 4% of total deaths [6], respectively. Type 2 diabetes is a continuing metabolic disorder that changes blood glucose levels and is usually a consequence of the body's ineffectiveness to employ its produced insulin [7], [8].…”
Section: Introductionmentioning
confidence: 99%